Current Nutrition Strategies in the Prevention and Management of Diabetes Mellitus - Anrian Junaedy Hasyuddin (Journal of Nutrition and Health Care, 2024)
Diabetes mellitus (DM) continues to be a significant global health challenge, requiring a comprehensive approach to its prevention and management. This study explores recent developments in customized nutritional strategies to address the complexities of DM. The study utilized an observational and experimental design, involving individuals diagnosed with DM. Data collection included health and nutrition surveys, laboratory analyses, and individualized nutrition interventions. Results showed substantial improvements in fasting and postprandial blood glucose levels, weight loss, and improved lipid profiles following the personalized nutrition intervention. The discussion emphasizes the effectiveness of personalized nutrition strategies, stressing the importance of an individualized approach and highlighting the positive impact on blood glucose control, weight management, and lipid profiles. The findings show promising implications for clinical practice, emphasizing the potential for developing more effective and individualized nutritional guidelines for the prevention and management of Diabetes Mellitus. Limitations and avenues for further research are discussed, emphasizing the need for a larger sample size and longer follow-up period. In conclusion, this study contributes valuable insights into the role of current nutritional strategies in the holistic management of Diabetes Mellitus, paving the way for improved personalized care and better outcomes.